Chapter 14 Pirate utopias? Viking camps and aspirational polities - Price, Neil (Taylor & Francis, 2023)
The Viking as pirate is one of the oldest interpretational tropes connected with the predatory maritime activities of the Scandinavian peoples between c.750-1050 CE. Over the past decade, however, this has gained new theoretical force through comparisons with paradigms of piracy drawn from later times and contexts, embracing the concept of hydrarchies and the notion of pirate communities as forming discrete social worlds. With their regional bases on the great rivers of Frankia, and the many winter camps of the British Isles, there is also another sense in which the Vikings prefigure the Early Modern pirates, in creating physical embodiments of their lifestyle by building special kinds of safe havens. Places like the Republic of Pirates in the Bahamas (1706-1718), and several others, were consciously politicised and modelled on the utopian communities created by writers such as Francis Bacon, Henry Neville, and of course, Thomas More. It is in this context that the chapter explores the archaeology of Viking camps: the mobile, multiethnic 'armies' which occupied them, their strategic interactions with local populations, and the workings of what anarchist thinkers have termed 'temporary autonomous zones'.